DOES CORPORATE SOCIAL RESPONSIBILITY ENHANCE RETURN ON ASSETS? EVIDENCE FROM MANUFACTURING FIRM IN NIGERIA - Carol, Nwankwo; Nnenna, Onyeka Virginia; Nnenna, Chukwuani Victoria (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The empirical research into the impact of CSR on return on assets is confusing and far from conclusive. Also in most ofthe previous studies; economic performance covered a (commonly five year) period surrounding the CSR performanceand/or social disclosure periods. To overcome these limitations, our paper assess the impact of CSR return on assets ofmanufacturing firms in Nigeria. The result showed that with CSR, corporate social responsibility had a positive and significant effect on return on assets of the manufacturing organizations while without CSR, the impact is negative and non-significant. The implication is that what companies spend on the development of society of interest may be related toreturn on equity but does not significantly detect increase/decrease in return on equity. This study thus posits thatmanufacturing organizations should concentrate evenly also on other elements which organization see mainly as majordeterminants of return on assets as the finding is showing an insignificant effect of CSR on ROA.